Pemanfaatan Puisi Anak sebagai Media Mitigasi Bencana - Siti Anafiah (LPPM Press, 2011)
This article is about a study explaining: 1) The elements of the childrenpoentry that could be use as the media for disaster’s mitigation; 2) compabilityand the accuracy of the child’s poentry for its prospective reader based on thecognitive development stage of the children; and formulated utilization planningof the children poentry to the disaster mitigation in Indonesian and literaturelearning. The children poentry studied are fiveten take in Bobo children magazine.The children poentry was taken through the purposive technique sampling. Thedata was analyzing by content analysis. The validity of the data was testedthrough the semantics validity and the reliability was tested by reading the textrepeatedly. The results of studied showed that: 1) The element that had thepotential to use as the planning media for the mitigation of disaster were thetheme, message, and sound; 2) Based on the use of the point of view, the writingtechnique (the language) and the explanation of the problem, the poentry exact tobe give to children age 8-12 years; and 3) the disaster mitigation efforts could becarried out by understanding the contents of the text, gave the response to theproblem of the disaster and the control as well as its prevention, or wrote thephenomenon of the natural or social disaster.